The critical role of biochar to mitigate the adverse impacts of drought and salinity stress in plants - Wu, Yanfang; Wang, Xiaodong; Zhang, Long; Zheng, Yongjie; Liu, Xinliang; Zhang, Yueting (Frontiers in Plant Science, 2023)
Drought stress (DS) is potential abiotic stress that is substantially reducing crop productivity across the globe. Likewise, salinity stress (SS) is also serious abiotic stress which is also a major threat to global crop productivity. The rapid climate change increased the intensity of both these stresses which is posing a serious threat to global food security therefore; it is urgently needed to tackle both these stresses to ensure better crop production. Globally different measures are being used to improve crop productivity under stress conditions. Among these measures, biochar (BC) has been widely used to improve soil health and promote crop yield under stress conditions. The application of BC improves soil organic matter, soil structure, soil aggregate stability, water and nutrient holding capacity, and activity of both beneficial microbes and fungi and leads to an appreciable increase in tolerance against both these damaging abiotic stresses by bringing favorable changes in changes in plant functioning. Likewise, BC biochar protects membrane stability, improves water uptake, and nutrient homeostasis, and reduces reactive oxygen species (ROS) production through enhanced anti-oxidant activities thereby substantially improve tolerance against both stresses. Moreover, BC mediated improvement in soil properties also substantially improves photosynthetic activity, chlorophyll synthesis, genes expression, the activity of stress-responsive proteins, and maintains the osmolytes and hormonal balance which in turn improve the plant's ability to with stand drought and salinity-induced osmotic and ionic stresses. In conclusion, BC could be a promising amendment to bring Therefore, in the present review, we have discussed various mechanisms through which BC improves tolerance against both drought and salinity stresses. The various research questions that are not still addressed have been also identified that must be addressed in future research studies. This review will bring will help to readers to learn more about the role of biochar to bring drought and salinity stress in plants and it will also provide on new suggestions on how this current knowledge about biochar can be used to develop drought and salinity tolerance.